2002
DOI: 10.1590/s0102-05362002000200006
|View full text |Cite
|
Sign up to set email alerts
|

Produção comercializável e teores de Cu e Zn em cenoura em decorrência da ação residual de fósforo e composto de lixo em solo sob cerrado

Abstract: Realizou-se em 1997, em condições de campo um experimento em Latossolo Vermelho Escuro distrófico argiloso sob cerrado de Brasília, para avaliar o efeito residual das aplicações em anos anteriores, a lanço de doses de fósforo (superfosfato triplo), e de composto de lixo na produção de cenoura (Daucus carota), cv. Brasília, assim como nos teores de cobre e zinco em raízes frescas. Aproveitou-se o mesmo delineamento experimental de blocos ao acaso com 3 repetições, no mesmo campo experimental dos experimentos an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
1
0
0
1
Order By: Relevance
“…Phosphate fertilization significantly increased carrot productivity, which was also significantly influenced by P sources (Figure 2b). Araújo et al (2004) also verified an increase of carrot productivity with phosphate fertilizer, and by the residual effect of doses up to 762.5 kg ha -1 P 2 O 5 and organic waste compost by Mesquita Filho et al (2002). The maximum productivities observed in this study with phosphate fertilizer were higher than the national average reported by Santos et al (2015), 31.0 t ha -1 , in 2014.…”
Section: Resultssupporting
confidence: 70%
“…Phosphate fertilization significantly increased carrot productivity, which was also significantly influenced by P sources (Figure 2b). Araújo et al (2004) also verified an increase of carrot productivity with phosphate fertilizer, and by the residual effect of doses up to 762.5 kg ha -1 P 2 O 5 and organic waste compost by Mesquita Filho et al (2002). The maximum productivities observed in this study with phosphate fertilizer were higher than the national average reported by Santos et al (2015), 31.0 t ha -1 , in 2014.…”
Section: Resultssupporting
confidence: 70%
“…Quando o solo é fertilizado com adubos orgânicos ricos em Cu e Zn, a liberação desses nutrientes ocorre à medida em que a matéria orgânica é decomposta e as plantas podem absorver esses nutrientes além do limite permitido para o consumo, especialmente se doses maiores de adubo orgânico forem utilizadas ou aplicações sucessivas forem feitas (Mesquita Filho et al, 2002).…”
Section: Resultsunclassified